797 IMPROVING GERIATRIC CARE IN THE EMERGENCY DEPARTMENT; TREATT PROJECT: THE RAPID EARLY ASSESSMENT THERAPY TEAM. (8th March 2022) - Foxley, H; Colby, C; Swin, J; Leyland, R
Abstract: Introduction: At University Hospital Southampton (UHS) on average 400 elderly patients attend the emergency department (ED) each month following a fall with an estimated cost to the NHS of £2.3 billion a year. 50% of over 80's fall at least once a year, after a first fall, 2/3 will fall again within the year. Since the creation of the Same Day Emergency Care (SDEC), treatment of those attending ED with frailty conditions has improved. However, the current therapy service cannot adequately assess these patients, leading to longer length of stay (LOS) and suboptimal functional outcomes. An initial 3-month pilot in ED identified those seen by a therapist had a reduced LOS compared with those who did not receive therapy (6.9 days vs 8.5 days). The data identified that 253 patients presenting later in the day received a substandard service. Methods: An extended hours trial across a 2-month period was conducted. During this period therapists provided a proactive, responsive service to support comprehensive geriatric assessments (CGAs) in ED. Data was collected including demographics, diagnosis, response time, interventions, community referrals and LOS. The key outcome measures identified within the pilot were LOS, reduction in 1 night hospital stays, appropriate onward referrals, readmission rates and CGAs including falls reviews. Results: This improvement project is in progress and the trial will be completed August 2021. The key areas for analysis will be LOS, readmission rates and the impact of early frailty assessments on discharge destination and admission avoidance. Conclusion: With the aging population and local demographics in West Hampshire and Southampton city, frailty conditions are increasing. The demand on ED outweighs the current therapy service. The trial aims to avoid multiple admissions following falls, improve patients' outcomes through reduced LOS and ensure appropriate referrals are made to ensure continuity of care into the community.